Creatine in humans with special reference to creatine supplementation - Balsom, P. D.; Soderlund, K.; Ekblom, B. (Sports Medicine, 1994)
Since the discovery of creatine in 1832, it has fascinated scientists with its central role in skeletal muscle metabolism. In humans, over 95% of the total creatine (Crtot) content is located in skeletal muscle, of which approximately a third is in its free (Crf) form. The remainder is present in a phosphorylated (Crphos) form. Crf and Crphos levels in skeletal muscle are subject to individual variations and are influenced by factors such as muscle fibre type, age and disease, but not apparently by training or gender. Daily turnover of creatine to creatininefor a 70kg male has been estimated to be around 2g. Part of this turnover can be replaced through exogenous sources of creatine in foods, especially meat and fish. The remainder is derived via endogenous synthesis from the precursors arginine, glycine and methionine. A century ago, studies with creatine feeding concluded that some of the ingested creatine was retained in the body. Subsequent studies have shown that both Crf and Crphos levels in skeletal muscle can be increased, and performance of high intensity intermittent exercise enhanced, following a period of creatine supplementation. However, neither endurance exercise performance nor maximal oxygen uptake appears to be enhanced. No adverse effects have been identified with short term creatine feeding. Creatine supplementation has been used to treat diseases where creatine synthesis is inhibited.